Joseph’s Tear: A Reading from Postcolonial Studies and Ethnicity Research Perspectives - WU, Chi-Te (Journal of Research for Christianity in China (JRCC), 2022)
The paper interprets the story of Joseph in Genesis using ethnicity research from a postcolonial perspective. Joseph comes from a nomadic background, yet he dreams of sheaves, which symbolize farming. This cultural mismatch kicks the story off. Then his identity as a Hebrew person is enlightened when he encounters ethnic boundary in the incident of Potiphar’s wife. He then becomes the middleman between the Egyptian empire and Jacob’s family. The whole storyline reveals Joseph as a “colonized intellectual”, with its special inner struggles and tensions. The paper then continues to discuss how the Egyptian empire tries to incorporate Jacob’s family. As a middleman, Joseph’s tear explains the consideration of a “colonized intellectual”, negotiating between the empire and the family. Joseph decides to do everything “for the survival of the family”. And this self-understanding causes him to have frictions with his brothers. He cannot be understood by them. The paper tries to show how a postcolonial reading and ethnicity research are helpful for interpreting the Bible for our time. It provides ways to approach complex relationships between the colonizers and the colonized.